2022
DOI: 10.2147/ppa.s326290
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Burdens and Educational Needs of Caregivers of People with Schizophrenia: Results of a National Survey Study

Abstract: Purpose Schizophrenia is a chronic, serious, and disabling mental disorder that affects how an individual thinks, feels, and behaves. With the availability of effective antipsychotic medications, the care of people with schizophrenia has shifted from psychiatric hospitals to outpatient treatment and caregivers, including family members. Caregivers are an often-overlooked target for education but may be a key resource to enhance patient education and foster greater adherence to treatment. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Clear communication and interaction between families and health professionals at an early stage of a patient's illness decrease family distress (Caqueo-Urízar et al, 2017); however, families are easily neglected in the treatment process. Most families of patients with schizophrenia reported that they received inadequate information regarding the illness, medication, symptoms, and coping strategies (Lippi, 2016) despite their interests and needs (Citrome et al, 2022). Thus, to increase the feasibility and application of FISs, continuing education or training programmes for health professionals to care for families of patients with schizophrenia will be essential.…”
Section: Control-bmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear communication and interaction between families and health professionals at an early stage of a patient's illness decrease family distress (Caqueo-Urízar et al, 2017); however, families are easily neglected in the treatment process. Most families of patients with schizophrenia reported that they received inadequate information regarding the illness, medication, symptoms, and coping strategies (Lippi, 2016) despite their interests and needs (Citrome et al, 2022). Thus, to increase the feasibility and application of FISs, continuing education or training programmes for health professionals to care for families of patients with schizophrenia will be essential.…”
Section: Control-bmentioning
confidence: 99%
“…As the tendency of institutional-based care has switched to community-and family-based care for those with disabilities in many countries, families are likely to undertake the responsibility of family members with the illness (Ko & Park, 2021;Koç et al, 2021). Globally, the primary caregivers of patients with schizophrenia are mostly family members, including parents, spouses, or siblings (Citrome et al, 2022;Lasebikan & Ayinde, 2013).However, caregiver roles in families are challenging. The family's roles are not limited to fulfilling the patients' basic needs (e.g., cooking, clothing, and cleaning).…”
mentioning
confidence: 99%
“…In a national survey, caregivers of patients with schizophrenia in the United States, who considered themselves responsible for the patient's adherence and treatment, identified fewer barriers with LAI use and viewed the patients as more capable of being treatment adherent when on LAIs. 88 As seen from data pooled from two large clinical trials, caregiver burden can be substantially reduced by switching from an oral antipsychotic to either PP1M or PP3M. 89 In the pragmatic REMISSIO study, patients stabilized on PP1M prior to the start of the study had mild-to-moderate caregiver burden, which reduced significantly (p<0.0001) when the patients were switched from PP1M to reduced dosing frequency with the longer acting PP3M.…”
Section: Effect Of Longer Acting Formulations On Caregiver Burdenmentioning
confidence: 99%
“…It also results in substantial personal distress. In addition to the fact that hospitals no longer have to shoulder the burden of care, caregivers and society also suffer significant immediate and long-term consequences, such as long-term psychosocial and economic support, frequent hospitalization, and work productivity loss throughout the patients' lifetime ( 1 ). In most cases, schizophrenia patients show signs of social impairment, which is a major cause of distress to caregivers and patients ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, schizophrenia patients show signs of social impairment, which is a major cause of distress to caregivers and patients ( 2 ). The emotional well-being of caregivers and the ability to lead a fulfilling personal and family life have all been reportedly affected by the illness ( 1 ). Besides, family caregivers experience stress and exhaustion due to the demanding task of providing care for schizophrenia patients over an extended period of time ( 3 ).…”
Section: Introductionmentioning
confidence: 99%